Editorial: Omics-driven crop improvement for stress tolerance, Volume II - Yi, Han; Weicong, Qi; Jian, Chen; Zhen, Li; Xiaofeng, Su; Freddy Yeo, Kuok San (Frontiers Media, 2024)
Crops are vulnerable to biotic and abiotic stresses that lead to reduced yields. Biotic stresses, such as fungi and pests, cause crops to rot and develop diseases. In contrast, abiotic stresses—such as high temperatures, salinity and mineral toxicity, and water shortages—irreversibly affect crops at different developmental stages, such as flowering, grain filling, and maturation through signal transduction, gene expression, and protein modifications. An increase of 1°C in the global average temperature is projected to significantly reduce crop yields. Excessive soil salinity tends to inhibit plant growth, hinder photosynthesis, and require metabolic adjustments. However, some crop types and species can tolerate modest levels of salinity without affecting their growth and yield. Drought is one of the most damaging abiotic stresses affecting severely the productivity of cereal crops. Rice struggles to survive in water-deficient fields, while maize is highly susceptible to drought. Therefore, improving crop stress tolerance is crucial for yield stability and healthy growth.